Photography and social movements - Memou, Antigoni (Manchester University press, 2013)
Now available for the first time in paperback, Photography and social movements is the first thorough study of photography’s interrelationship with social movements. Focusing on photographic production and dissemination during the student and worker uprising in Paris in May 1968, the Zapatista rebellion, and the anti-capitalist protests in Genoa in 2001, the book argues that at times of political uprisings, photographic documentations, often contradictory, strive to prevail in the public domain, extending the political or economic struggle to a representational level. Photography plays a central role in this representational conflict, by either reproducing or challenging stereotypical narratives of protest. This groundbreaking interdisciplinary analysis of a wide range of practices - amateur and professional - and of previously unpublished archival material will add considerably to students’, researchers’ and scholars’ knowledge of both the visual imagery of political movements and the developing history of photographic representation.